Community response to the foreclosure crisis: Thoughts on local interventions - Dan Immergluck (University of California, Institute of Urban and Regional Development (IURD), 2008)
The purpose of this paper is to lay out the range of responses to the foreclosure crisis in which local organizations have been engaged in recent years, providing a scheme for thinking about local responses to the crisis and the actors and organizations involved. It is also intended to help groups identify where responses in their community might be expanded or strengthened. It is important to point out here that the paper generally does not address efforts to reduce high-risk lending in communities or to improve access to sound and affordable mortgage credit. While these are critically important and complementary strategies, they are beyond the scope of this paper.
Keywords: 330